Stress analysis of over-denture abutments treated with two obturation techniques - Ahmed N. Elsherbini; Mohamed M Nagy; Nancy N Elsherbini (University Library System, University of Pittsburgh, 2021)
Aim: Evaluation of stresses induced on over-denture abutments endodonticaly treated with two different obturation techniques. Materials and methods: eight mandibular permanent canines were inserted in four pesudo-realistic models.  In each model two canines were placed in it. One canine was treated with lateral obturation technique and the other canine with vertical obturation technique. Four over-denture prostheses were fabricated on the four models. Then strain gauges were attached on the coronal one third of the root buccally and lingually for all eight canines. A metal rod was placed occlusally on the premolar -molar area, and a 50 N load was applied on the middle of the rod using the universal testing machine. Readings were collected. Results: from the collected data the lateral obturation showed 85.25±104.901 µε and the vertical obturation showed 4.875±3.555 µε with significance difference of P<0.05 between the groups. Conclusion: it can be concluded that the abutments treated with vertical obturation techniques reduced the stresses induced to the supporting structures when compared with the lateral condensation technique.